Comparison of Interval Estimators of Pr(X < Y) in the Two-parameter Exponential Distribution - Baklizi, Ayman (Communications in statistics. Simulation and computation, 2016)
We consider confidence intervals for the stress-strength reliability Pr(X< Y) in the two-parameter exponential distribution. We have derived the Bayesian highest posterior density interval using non-informative prior distributions. We have compared its performance with the intervals based on the generalized pivot variable intervals in terms of their coverage probabilities and expected lengths. Our simulation study shows that the Bayesian interval performs better according to the criteria used, especially when the sample sizes are very small. An example is given.